Exposure to the smell and taste of milk to accelerate feeding in preterm infants - Muelbert, Mariana (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine whether exposure to the taste or smell (or both) of milk administered with tube feedings can accelerate progress to full sucking feeds without adverse effects in preterm infants. We will also assess these effects in subgroups with different modes of administration, gestational age, birthweight, and type of milk.